گل خان نصیر ءُ عبدالرحمٰن کرد ءِ عملی زندءُ شاعری ءَ ہمگونگی: Similarities in poetry and personalities between Gull khan Naseer and Abdul Rehman Kurd - Yousuf, Muhammad; Sabir, Gulam Dastageer (Hanken, 2013)
Comparison of two great personalities or poets regarding their intellectual or poetic work is not a small job. One can compare the poetic works of a poet, when their interests, nationalistic approach, grievances, society, outskirts and the national values are same. This paper focuses the similarities of the poetic works of the great Balochi poet Mir Gul Khan Naseer and Babu Abdul Rehman Kurd. It also illustrates the nationalistic, poetic and national grievances of both great poets